Lock-in and its influence on the project performance of large-scale transportation infrastructure projects: investigating the way in which lock-in can emerge and affect cost overruns - Cantarelli, C; Flyvbjerg, B; van Wee, B; Molin, E (2010)
Lock-in, the escalating commitment of decision makers to an ineffective course of action, has the potential to explain the large cost overruns in large-scale transportation infrastructure projects. Lock-in can occur both at the decision-making level (before the decision to build) and at the project level (after the decision to build) and can influence the extent of overruns in two ways. The first involves the ‘methodology’ of calculating cost overruns according to the ‘formal decision to build’. Due to lock-in, however, the ‘real decision to build’ is made much earlier in the decision-making process and the costs estimated at that stage are often much lower than those that are estimated at a later stage in the decision-making process, thus increasing cost overruns. The second way that lock-in can affect cost overruns is through ‘practice’. Although decisions about the project (design and implementation) need to be made, lock-in can lead to inefficient decisions that involve higher costs. Sunk costs (in terms of both time and money), the need for justification, escalating commitment, and inflexibility and the closure of alternatives are indicators of lock-in. Two case studies, of the Betuweroute and the High Speed Link-South projects in the Netherlands, demonstrate the presence of lock-in and its influence on the extent of cost overruns at both the decision-making and project levels. This suggests that recognition of lock-in as an explanation for cost overruns contributes significantly to the understanding of the inadequate planning process of projects and allows development of more appropriate means.